PELAKSANAAN PENGENALAN LAPANGAN PERSEKOLAHAN (PLP) IAI HIDAYATULLAH BATAM di PPS ULA IMAM SYAFI’I BATAM - Riyadhi Salim; Usama Saiful Haq; Ahmad Syabili Bin Muhardi; Domi Saputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to determine the school environment. The Introduction to the School Field (PLP) was carried out on January 5 to February 13 at PPS Ula Imam Syafi'i Batam with 3 members including, Ahmad Syabili, Usamah Saiful Haq, Riyadhi Salim. In implementing school field experience (PLP) there is several work carried out to add experience and intellectual knowledge for us to learn as students. During the Introduction to Schooling Field (PLP), the activities carried out include accompanying and observing students during the learning process, and participating in various activities held at school.